Qualitative survey of the entomofauna in a semideciduous seasonal sorest remnant - Lima, Júlio César dos Santos (Revista Ambientale, 2023)
The Atlantic Forest has only 8.5% of its forest remnants and in the state of São Paulo, one of its phytophysiognomies, the Semideciduous Seasonal Forest, has registered accelerated and continuous deforestation, remaining for few areas still preserved, in parks, reserves or on private properties. Insects develop several ecological functions within these systems and are considered good indicators of environmental impacts and important members of biological processes. The objective of the present study was to carry out a preliminary qualitative survey of the diversity of entomofauna in a forest remnant, using the scanning method and photographic record, and to analyze the correlation between the number of specimens recorded and some climatological variables. A total of 213 individuals were registered, distributed among 14 orders and 85. Coleoptera was the most represented order with 64 records. Climatological variables, maximum and minimum temperature, rainfall and relative humidity did not influence the number of organisms. The species richness registered in this study constitutes an immeasurable natural resource, and, therefore, the preservation of this area becomes justifiable, not only because it is contained in a State Park, but also because of its genetic heritage.